Electroanalytical Assessment of Heavy Metals in Waters with Bismuth Nanoparticle-Porous Carbon Paste Electrodes. (20th May 2015) - Niu, Pengfei; Fernández-Sánchez, César; Gich, Martí; Ayora, Carlos; Roig, Anna
Graphical abstract: Highlights: A bismuth carbon nanocomposite material prepared by a one-pot sol-gel process. Application to the fabrication of a sensor for heavy metal detection in waters. Cd, Pb and Ni were measured at concentration levels below the MAC-EQS set by the EU. Thorough assessment of the sensor performance in water samples of different origin. Abstract: This work reports on a detailed analytical assessment of a bismuth nanoparticle- porous carbon paste electrode working as an electrochemical sensor for the sensitive detection of Cd(II), Pb(II) and Ni(II) in water samples of different origin. Detection limits of 0.81, 0.65 and 5.47 ppb for Cd(II), Pb(II) and Ni(II), were achieved, respectively, keeping the overall analysis time below 240 s. This sensor device was employed in the analysis of several contrasting samples such as tap water, ground water, polluted waters from an influent and effluent of an urban wastewater treatment plant and polluted river water due to acid mine drainages, thereby covering a wide spectrum of matrices and absolute and relative heavy metal concentrations. Results were shown to be in good agreement with the reference values. The one-pot mass production of this composite material and the use of Bi in the form of nanoparticles result in sensitive, reproducible and cost-effective electrochemical devices. Moreover, the sol–gel synthesis technology applied to the production of the electrode material can be easily adapted to the fabrication of thick or thin films on planar substrates for the development of electrochemical sensors that could be of practical use for the on-site heavy metal analysis in diverse water sources.